The effect of corporate governance, tax avoidance, and profitability on earnings management - Tri Siwi Nugrahani; Yuni Purwanti; Rifqi Muhammad; Evi Grediani (Jurnal Akuntansi dan Auditing Indonesia)
Using an agency theory approach, this study examines the influence of institutional ownership, managerial ownership, tax avoidance, and profitability on earning management. There are 315 companies as a research sample using the purposive sampling method with the following criteria: companies listed on the IDX during the 2018-2022 period, companies that prepare annual financial statements, and non-cyclical consumer sector companies. This study used multiple linear regression analysis and a t-test with a significance of 5% as hypothesis testing. The results of the study show that institutional ownership, managerial ownership, and tax avoidance have a negative effect on earning management, while profitability has a positive effect on earning management. These results prove that institutional and managerial ownership and good corporate governance can reduce earning management and tax avoidance. However, profitability still improves earning management.